Sami'na Wa Atha'na Concepts of Education in Humanistic Learning Theory Perspectives - Amir Bandar Abdul Majid; Suyadi (Tarbiyah Departement collaboration with AMCA, 2021)
The purpose of this research is to find humanistic values in pesantren education that traditionally still use sami'na wa atha'na habits. This research is a type of qualitative research that uses a descriptive approach. The form of data presentation is taken from pesantrens in Yogyakarta, namely Pondok Al-Munawwir Kerapyak, Pondok Ulul Albab Balirejo, and Pondok Wahid Hasyim Nologaten. The results showed that humanistic education can be applied in pesantrens and not Contrary to the Qu'an and Hadith . Humanistic education in its development in pesantren is divided into three, namely 1) Humanistic based on purpose; 2) Humanistic based process; 3) Humanistic based on pesantren curriculum.